The Role of Brand Awareness in Mediation: the Effect of Promotion Mix on Purchase Intention at Hotel Aloft Bali Seminyak - Maysitha, Ni Putu Shasya Ayu; Suastini, Ni Made (Asian Journal of Management Analytics, 2023)
Hotel competition during the COVID-19 pandemic has encouraged hotels to maximize their marketing strategies to influence consumer behavior. This study was conducted to determine the direct effect of the promotion mix on purchase intention and the indirect effect mediated by the brand awareness variable at the Aloft Hotel Bali Seminyak which has a new existence. The method used is quantitative and distributes questionnaires to 100 respondents who are determined through the unknown population formula. The data analysis technique used descriptive statistical analysis and path analysis. The researcher found that the promotion mix and brand awareness had a positive and significant effect on purchase intention, the promotional mix had a positive and significant effect on brand awareness.